Indefinitely Oscillating Functions-Part I - T. El Bouayachi; N. Yebari (International Journal of Mathematics And its Applications, 2016)
This article details a class of indefinitely oscillating functions in $H^{s}(% \mathbb{R})$. It is a class of functions of the Sobolev space $H^{s}(\mathbb{% R})$ which have for all $m$ integer one primitive of the order $m$ in the same space.